2014
DOI: 10.1017/s037689291400023x
|View full text |Cite
|
Sign up to set email alerts
|

Marine ecological footprint indicates unsustainability of the Pohnpei (Micronesia) coral reef fishery

Abstract: SUMMARYThroughout the tropics, developing countries and territories are highly dependent on nearshore marine resources for food and income, however information on the sustainability and proper management of these fisheries is lacking. In Pohnpei, Micronesia, the sustainability of a coral reef finfishery was assessed by comparing coral reef fish demand to coral reef biocapacity using a marine ecological footprint (MEF) analysis. Based on geo-referenced satellite and aerial imagery, Pohnpei and surrounding atoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(80 reference statements)
1
4
0
Order By: Relevance
“…We found that the densities of herbivorous fish were generally low, consistent with previous observations on Micronesian reefs (Mumby et al 2013). The Micronesian reef fisheries are not sustainably managed (Houk et al 2012, Rhodes et al 2015, and fish densities could be related to the presence of human settlements on the islands as well as foreign fishing interests. Herbivorous fish abundances were highest on the most populated islands of Pohnpei and Yap (Table 1), suggesting that local management practices that protect herbivorous fish are having a measurable impact.…”
Section: Context Of Micronesian Reefs and Nutrient And Organic Matter Concentrationssupporting
confidence: 88%
“…We found that the densities of herbivorous fish were generally low, consistent with previous observations on Micronesian reefs (Mumby et al 2013). The Micronesian reef fisheries are not sustainably managed (Houk et al 2012, Rhodes et al 2015, and fish densities could be related to the presence of human settlements on the islands as well as foreign fishing interests. Herbivorous fish abundances were highest on the most populated islands of Pohnpei and Yap (Table 1), suggesting that local management practices that protect herbivorous fish are having a measurable impact.…”
Section: Context Of Micronesian Reefs and Nutrient And Organic Matter Concentrationssupporting
confidence: 88%
“…In Pohnpei, marine resources are managed under an open access system that allows fishers access to any reef area. This arrangement, together with night‐time spearfishing, has contributed to widespread declines in coastal marine resources (Rhodes et al, 2015). In spite of overall declines, a few private landowners and communities have made some progress towards conserving resources in localized areas.…”
Section: Discussionmentioning
confidence: 99%
“…Limitations on catches have become necessary to allow marine ecosystems to rebuild their productive potential and biodiversity, protecting juveniles and reproductively active fishes. If we continue altering marine food networks, we will not be able to fish as we did in the past [15,40].…”
Section: Discussionmentioning
confidence: 99%
“…Although the Marine Ecological Footprint is not able to express all the problems related to the marine ecosystem, such as pollution levels of the fish, it appears anyway to be a tool that allows people to understand and communicate in an immediate way the environmental impact concerning the consumption of fish and other marine-based products and services by humans and, thanks to these characteristics, it appears to be an easily understood metric for policymakers to gauge demand and associated impacts but also the behavior of individual consumers [15].…”
Section: Literature Review and Analysis Of Indicatorsmentioning
confidence: 99%